2016
DOI: 10.1177/1098612x15602738
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pain control in cats: clinical trials with pre-emptive lidocaine epidural co-administered with morphine or methadone

Abstract: Objectives The aim of the study was to evaluate the effectiveness of epidural lidocaine in combination with either methadone or morphine for postoperative analgesia in cats undergoing ovariohysterectomy. Methods Under general anesthesia, 24 cats that underwent ovariohysterectomy were randomly allocated into three treatment groups of eight each. Treatment 1 included 2% lidocaine (4.0 mg/kg); treatment 2 included lidocaine and methadone (4.0 mg/kg and 0.3 mg/kg, respectively); and treatment 3 included lidocaine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 24 publications
2
15
1
1
Order By: Relevance
“…Lee et al (2004) corroboram a assertiva ao atestarem progressão entre T7 e T11 relativa à administração de 0,3mL/kg de azul de metileno no espaço epidural (L7-S1) de felinos. Em estudo recente, o uso epidural (L7-S1) de lidocaína associada à morfina ou à metadona em volume final de 0,25mL/kg, determinou analgesia adequada e prolongada em felinas submetidas à OSH (DeRossi et al, 2016). Complementarmente, a associação tramadollidocaína, em doses idênticas à do estudo em pauta, demonstrou analgesia superior ao uso do anestésico local isolado, com propagação cranial satisfatória (T13-L1) em felinas (Hermeto et al, 2015).…”
Section: Resultsunclassified
“…Lee et al (2004) corroboram a assertiva ao atestarem progressão entre T7 e T11 relativa à administração de 0,3mL/kg de azul de metileno no espaço epidural (L7-S1) de felinos. Em estudo recente, o uso epidural (L7-S1) de lidocaína associada à morfina ou à metadona em volume final de 0,25mL/kg, determinou analgesia adequada e prolongada em felinas submetidas à OSH (DeRossi et al, 2016). Complementarmente, a associação tramadollidocaína, em doses idênticas à do estudo em pauta, demonstrou analgesia superior ao uso do anestésico local isolado, com propagação cranial satisfatória (T13-L1) em felinas (Hermeto et al, 2015).…”
Section: Resultsunclassified
“…The groups that received only lidocaine (ELG) and only maropitant (EMG) required rescue analgesia two hours into the post-operative period, while the group that received both maropitant and lidocaine (ELMG) required rescue analgesia three hours after the operation. While evaluating the use of lidocaine through epidural administration, previous studies (DeRossi et al, 2016) also observed that the animals that received only lidocaine required rescue analgesia after two hours in the postoperative period. These results are similar in female dogs subjected to ovariohysterectomy that received only lumbosacral epidural lidocaine (Hermeto et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Research, Society and Development, v. 11, n. 7, e17511729612, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i7.29612 3 The use of epidural analgesics is advantageous because of long duration of action and the low required doses (Castro et al, 2009). In cats and dogs, both anesthesia and analgesia through the epidural space can be used for both elective and emergency surgical procedures (Robertson & Taylor, 2004;Valverde, 2008;DeRossi et al, 2016;Fernandez-Parra et al, 2017;Steagall et al, 2017). Although some drugs such as α2-adrenergic agonists and ketamine are used for the purpose of analgesia, opioids are used more frequently (Valverde, 2008;Steagall et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Epidural anaesthesia allows postoperative pain management with the use of different drugs, such as opioids, local anaesthetics or α2--adrenoceptor agonists (DeRossi et al 2016;Steagall et al 2017;Garcia-Pereira, 2018). Although it is a commonly used technique, complications such as hypotension, bradycardia, ventilatory depression or urinary retention have been reported (Jones, 2001;Cerasoli et al 2017).…”
Section: Introduction ( Word Count 4127)mentioning
confidence: 99%